2012
DOI: 10.1073/pnas.1117135109
|View full text |Cite
|
Sign up to set email alerts
|

High-grade serous ovarian cancer arises from fallopian tube in a mouse model

Abstract: Although ovarian cancer is the most lethal gynecologic malignancy in women, little is known about how the cancer initiates and metastasizes. In the last decade, new evidence has challenged the dogma that the ovary is the main source of this cancer. The fallopian tube has been proposed instead as the primary origin of high-grade serous ovarian cancer, the subtype causing 70% of ovarian cancer deaths. By conditionally deleting Dicer, an essential gene for microRNA synthesis, and Pten, a key negative regulator of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
321
1
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 351 publications
(338 citation statements)
references
References 41 publications
13
321
1
3
Order By: Relevance
“…It is now believed that dissemination of serous cancers may occur by exfoliation of tumor cells originating from the distally located TICs (reviewed in [7]). Recent mouse models have shown transformation of human and mouse fallopian tube tissue into serous cancers through multiple genetic mutations [35,37]. These data suggest that serous cancers may arise from the fallopian tube.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…It is now believed that dissemination of serous cancers may occur by exfoliation of tumor cells originating from the distally located TICs (reviewed in [7]). Recent mouse models have shown transformation of human and mouse fallopian tube tissue into serous cancers through multiple genetic mutations [35,37]. These data suggest that serous cancers may arise from the fallopian tube.…”
Section: Discussionmentioning
confidence: 85%
“…The FTE is actively being explored as a site of initiation for serous cancers [35][36][37]. Dysplastic lesions identified typically in the distal end of the fallopian tube have been hypothesized to be precursor lesions for invasive serous cancers [38][39][40][41].…”
Section: Ftescs Are Expanded In the Fallopian Tube Epithelium Of Patimentioning
confidence: 99%
“…This is consistent across both the TCGA dataset (7/304) and our own local tumour bank (6/290; see supplementary material, Tables S1, S7). DICER1 hotspot mutations, although rare, were also identified in brain, colorectal and thyroid cancers (see supplementary material, TableDICER1 hotspot mutations in endometrial cancer 223 tumourigenesis beyond the spectrum of rare paediatric cancers [8][9][10][11][12][13][15][16][17][18]. DICER1 hotspot mutations and subsequent miRNA/mRNA dysregulation may therefore constitute a common oncogenic pathway in a small subset of endometrial tumours.…”
Section: Discussionmentioning
confidence: 99%
“…We identified an atypical hotspot mutation, G1809R, which is immediately adjacent to the metal-binding residue D1810, and characterized its functional impact on miRNAs and downstream signalling pathways. Using a Dicer1-null mouse fallopian tube carcinoma-derived cell line [17], we demonstrated that DICER1 hotspot mutations abolish the inhibitory effects of DICER1 on cell proliferation. Our data also suggested that loss of let-7 family miRNAs may contribute to the oncogenic properties of DICER1 hotspot mutations.…”
Section: J Chen Et Almentioning
confidence: 96%
See 1 more Smart Citation